Determinants of Financial Empowerment Among Women in Saudi Arabia - Ali, Murad; Ali, Imran; Badghish, Saeed; Soomro, Yasir A. (Frontiers in Psychology, 2021)
Increasing women’s financial empowerment is important as they experience a lack of control over economic resources as compared to men. Although plenty of research evidence is available on the determinants of financial empowerment among women in the developed countries, there is less known in the context of a traditionally male-dominated society like Saudi Arabia. The current study proposes a conceptual model that examines the role of financial literacy and financial socialization, in the development of financial self-efficacy, financial coping behaviors, and financial empowerment among Saudi women using social cognitive theory (SCT). Data is collected through a baseline survey from a sample of 1368 women respondents that belongs to the different segments of society ranging from female university students to households to women working in different sectors in Saudi Arabia. We employed Partial Least Squares (PLS) path modeling techniques using SmartPLS to test the hypotheses proposed in this study. The study found a significantly positive association between financial literacy, financial coping behavior, and financial wellbeing. Financial socialization is also significantly related to financial self-efficacy, and financial empowerment. We also found the positive role of financial self-efficacy, and financial coping behaviors in the development of financial empowerment. The practical implication of this study includes the provision of financial literacy education/training to Saudi women and increasing their financial socialization to improve their financial wellbeing.